2021
DOI: 10.1177/20539517211021437
|View full text |Cite
|
Sign up to set email alerts
|

Analysing discourse around COVID-19 in the Australian Twittersphere: A real-time corpus-based analysis

Abstract: Public discourse about the COVID-19 that appears on Twitter and other social media platforms provides useful insights into public concerns and responses to the pandemic. However, acknowledging that public discourse around COVID-19 is multi-faceted and evolves over time poses both analytical and ontological challenges. Studies that use text-mining approaches to analyse responses to major events commonly treat public discourse on social media as an undifferentiated whole, without systematically examining the ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…We used an extended database export to cover entries with at least 10,000 inhabitants (see Supplementary File for detailed information on matches/non-matches for each language). Relying on "location" fields to geolocate Twitter users is an established approach in social scientific research (for example, Bruns & Enli, 2018;Bruns et al, 2017;Rauchfleisch et al, 2021;Schweinberger et al, 2021;Vogler et al, 2019). However, some groups of users might be more inclined to disclose their location than others.…”
Section: Time Frame and Collection Of Tweetsmentioning
confidence: 99%
“…We used an extended database export to cover entries with at least 10,000 inhabitants (see Supplementary File for detailed information on matches/non-matches for each language). Relying on "location" fields to geolocate Twitter users is an established approach in social scientific research (for example, Bruns & Enli, 2018;Bruns et al, 2017;Rauchfleisch et al, 2021;Schweinberger et al, 2021;Vogler et al, 2019). However, some groups of users might be more inclined to disclose their location than others.…”
Section: Time Frame and Collection Of Tweetsmentioning
confidence: 99%
“…6,1214 A growing body of researchers have shown that sentiment analysis and topic modeling can be used to successfully investigate emotions and sentiment using natural language processing. 13,1517 Schweinberger et al 15 chose to model topics and sub-topics across different phases of the pandemic. Singh et al 18 demonstrated that Twitter conversations may be used to predict the spread and outbreak of COVID-19.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A special influence on constructing the media discourse had one sector of the media plane, which is social media. The existing body of research on COVID-19 and social media discourse has been mainly oriented toward Twitter (Damiano & Catellier, 2020;Chen et al, 2020;Schweinberger et al, 2021). Since Twitter is considered to provide researchers the opportunity of studying the role of social media in global health crisis (Chen et al, 2020;Lecompte-Van Poucke, 2022), but also there are several research papers which focus on social media plane in general (Gupta et al, 2022;Han et al, 2020).…”
Section: Theoretical Backgroundmentioning
confidence: 99%